Pendampingan Digital Marketing Dan Rebranding Produk UMKM “OPAK GAPIT” - Evan Saka Akhfan; Fani Khoirotunnisa (Jurnal Pengabdian Masyarakat Nusantara, 2023)
UMKM are an important sector to build the community's economy. During the COVID-19 pandemic in Indonesia, the economic situation of the community has decreased and has become a prolonged problem that must be resolved immediately. During the pandemic, UMKM owners experienced a buyer crisis which resulted in many UMKM players going out of business due to falling income. This happened in Talang Village which was affected by the COVID-19 pandemic. Digital marketing strategies can be done under any conditions. In Talang Village, Rejoso District, Nganjuk Regency, two UMKM have been registered with the government. One of them is the Opak Gapit Talang UMKM which already has a Business License Number (NIB) but the scope of the sales market is still small. There are several obstacles experienced such as lack of knowledge about digital marketing. With the right strategy will be able to compete with other snack products.